My gun, my brother : the world of the Papua New Guinea colonial police, 1920-1960 - Kituai, August Ibrum K., 1950- (Pacific islands monograph series, 1998)
Despite the heated competition for colonial possessions in Papua New Guinea during the nineteenth and early twentieth centuries, the personnel required to run an effective administration were scarce. As a result, the Australian colonial regime opted for a quick solution: it engaged Papua New Guineans--often to perform the most hazardous and most unpopular responsibilities. Based on extensive interviews with former policemen, written records of the time, and reminiscences of colonial officials, this book links events involving police, villagers, and government officers (kiaps) over a forty-year period to wider issues in the colonial history of Papua New Guinea and, by extension, of the Pacific Islands and beyond.